Resuscitative endovascular balloon occlusion of the aorta for uncontrollable nonvariceal upper gastrointestinal bleeding. Issue 1 (December 2016) - Sano, Hidefumi; Tsurukiri, Junya; Hoshiai, Akira; Oomura, Taishi; Tanaka, Yosuke; Ohta, Shoichi
Abstract Background Although resuscitative endovascular balloon occlusion of the aorta (REBOA) in various clinical settings was found to successfully elevate central blood pressure in hemorrhagic shock, this intervention is associated with high mortality and may represent a last-ditch option for trauma patients. We conducted a retrospective study of patients with nonvariceal upper gastrointestinal bleeding (UGIB) who underwent REBOA to identify the effectiveness of REBOA and reviewed published literatures. Methods REBOA were performed by trained acute care physicians in the emergency room and intensive care unit. The deployment of balloon catheters was positioned using ultrasonography guidance. Collected data included clinical characteristics, hemorrhagic severity, blood cultures, metabolic values, blood transfusions, REBOA-related complications and mortality. A literature search using PUBMED to include "aortic occlusion" and "gastrointestinal bleeding" was conducted. Results REBOA was attempted in eight patients among 140 patients with UGIB and median age was 66 years. Systolic blood pressure significantly increased after REBOA (66 ± 20 vs. 117 ± 45 mmHg, p  < 0.01) and the total occlusion time of REBOA was 80 ± 48 min. Strong positive correlations were found between total occlusion time of REBOA and lactate concentration (Spearman'sr =0.77), clinical Rockwall score (Spearman'sr =0.80), and age (Spearman'sr =0.88), respectively. Conclusion REBOA can be performed with a high degree of technical success and is effective at improving hemodynamic in patients with UGIB. Correlations between total occlusion time and high lactate levels, clinical Rockall score, and age may be important for successful use of REBOA.